Experimental study on mechanical response of soft soil freezing in underground excavation using artificial ground freezing method - Lu Han; Lingbing Yi; Peng Zhang; Lujie Chai; Ziming Cheng (PLoS ONE, 2026)
To ensure the stability of the artificial frozen wall during the underground excavation of a proposed subway station using the artificial ground freezing method in soft soil strata, and to guarantee the construction safety of the proposed station under-crossing beneath an existing operating station. Based on the project of a proposed subway station under-crossing an existing station via underground excavation with artificial ground freezing method, four typical soft soils, namely silty clay, mucky soil, residual cohesive soil, and fully weathered ignimbrite, were selected to conduct systematic physical and mechanical tests of frozen soil under the temperature range of −20°C to −5°C. The influence mechanism of temperature and confining pressure on the thermodynamic behavior of frozen soil was revealed through the transient hot wire method, unidirectional frost heave and thaw settlement test, and triaxial shear test. The results show that the thermal conductivity of soil samples increases significantly at low temperatures, with the largest increase observed in fully weathered ignimbrite and the smallest in mucky soil. The freezing temperature of soil samples under natural moisture content ranges from −2.25°C to −0.8°C, with the lowest value recorded for residual cohesive soil. The creep of frozen soil exhibits obvious stress dependence: it presents typical three-stage creep characteristics at the stress level of 0.5σs, and its long-term strength is approximately 0.5–0.7 times the instantaneous strength. In engineering practice, lower freezing temperature or strict control of loading duration should be adopted for soil layers with high creep potential. The triaxial shear strength of frozen soil increases with the decrease of temperature, and the most significant increase occurs in the temperature range of −5°C to −10°C. The strength of the tested soils ranks as follows: fully weathered ignimbrite > residual cohesive soil > silty clay > mucky soil. The influence of confining pressure on strength varies with soil types. During construction, differentiated freezing and support control measures shall be implemented according to the characteristics of soil layers, and monitoring shall be strengthened for sections with abnormal confining pressure response. The research results can provide an important basis for design optimization and construction risk control of subway underground excavation projects using artificial ground freezing method in soft soil areas.